Dual purpose hafnium oxide nanoparticles offer imaging Streptococcus mutans dental biofilm and fight it In vivo via a drug free approach. (October 2018) - Ostadhossein, Fatemeh; Misra, Santosh K.; Tripathi, Indu; Kravchuk, Valeriya; Vulugundam, Gururaja; LoBato, Denae; Selmic, Laura E.; Pan, Dipanjan
Abstract: The removal of tenacious dental plaque is of paramount importance; however, early diagnosis can be a challenging task in dental clinics due to the limitations of current approaches, specifically X-ray-based techniques. We have approached this problem by integrating antibacterial properties and X-ray contrast enhancement in a single probe specific to colonies of Streptococcus mutans as the most predominant and carious oral bacteria. We report the synthesis of an inherently therapeutic polymeric silane conjugated hafnium oxide nanoparticles (Hf PS NPs). Using a high-affinity pathogen-selective peptide, the concept of molecularly targeted X-ray imaging of cariogenic pathogen S. mutans was demonstrated. Ex vivo studies using extracted human tooth demonstrated striking X-ray attenuation of NPs vs. tooth. Additionally, Hf PS NPs exhibited significant bactericidal properties against cariogenic pathogen. Electron microscopy revealed that the antibacterial activity occurred via a 'latch and kill' mechanism. Mechanistic studies determined that these NPs fragmented bacterial DNA components to exert their antimicrobial effect. Importantly, Hf PS NPs effectively inhibited the growth of a mature biofilm on an ex vivo human tooth model. Finally, the NPs were applied to the rodent model of dental biofilm. Topical administration of the Hf PS NPs for 8 days (1X daily) could effectively attenuate the S. mutans biofilm challenge. This report is the first of its kind to demonstrate that HfO2 -based NPs can be used for simultaneous diagnosis and antibacterial treatment without requiring an additional drug.